2021
DOI: 10.1155/2021/6699560
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Pivotal Immunomodulatory and Anti-Inflammatory Potentials of Glycyrrhizic and Glycyrrhetinic Acids

Abstract: Licorice extract is a Chinese herbal medication most often used as a demulcent or elixir. The extract usually consists of many components but the key ingredients are glycyrrhizic (GL) and glycyrrhetinic acid (GA). GL and GA function as potent antioxidants, anti-inflammatory, antiviral, antitumor agents, and immuneregulators. GL and GA have potent activities against hepatitis A, B, and C viruses, human immunodeficiency virus type 1, vesicular stomatitis virus, herpes simplex virus, influenza A, severe acute res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(63 citation statements)
references
References 145 publications
0
63
0
Order By: Relevance
“…Glycyrrhiza glabra L., known as licorice, has shown nutritional and pharmacological properties especially assigned to glycyrrhizin 11 . Another isolated compound, the glycyrrhizic acid (GA), has been used regarding its antitumor, antiallergic, antibiotic and anti-inflammatory properties [12][13][14] . Dipotassium glycyrrhizinate (DPG), a secondary product of GA, has antiallergic, antibiotic and anti-inflammatory effects similar to the corticosteroids' ones, but without side effects, as skin allergic reactions 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…Glycyrrhiza glabra L., known as licorice, has shown nutritional and pharmacological properties especially assigned to glycyrrhizin 11 . Another isolated compound, the glycyrrhizic acid (GA), has been used regarding its antitumor, antiallergic, antibiotic and anti-inflammatory properties [12][13][14] . Dipotassium glycyrrhizinate (DPG), a secondary product of GA, has antiallergic, antibiotic and anti-inflammatory effects similar to the corticosteroids' ones, but without side effects, as skin allergic reactions 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…IFN is a broad-spectrum antiviral glycoprotein, which acts as a trigger, regulator, and effector of the immune system to participate in many physiological responses in virus infection ( Malmgaard, 2004 ), and it is the most important cytokine ( Richard, 2021 ). QFPDD upregulates the expression of IFN and interferon-stimulated genes (ISGs), and acts on the early stage of SARS-CoV-2 virus infection ( Wang et al, 2021a ).…”
Section: Research Status Of Antiviral Tcmsmentioning
confidence: 99%
“…Glycyrrhizin has long been known as a compound with many biological effects: antiinflammatory, antiulcer, antianaphylaxis, antioxidant, immunoregulatory, membrane stabilization, antiviral, and anticancer activities [4]. In particular, the anti-inflammatory activity of glycyrrhizic acid has been well studied; several in vitro studies have shown that glycyrrhizic acid can inhibit the production of the most proinflammatory cytokine such as TNF-α, interleukins IL-1β, and IL-6 [5]. Sun et al showed that glycyrrhizic acid inhibits the synthesis of nitric oxide and some inflammatory cytokines in microglial cells treated with LPS [6].…”
Section: Introductionmentioning
confidence: 99%